PERBANDINGAN PERILAKU HARIAN BURUNG BAYAN JANTAN (Eclectus roratus Müller, 1776) BERDASAKAN KEBERADAAN PEJANTAN PESAING DI TAMAN MARGASATWA RAGUNAN - DESMUDZAT, ANDES SACHRAN; SUKANDAR, PASKAL; SURYANDA, ADE (Bioma, 2015)
ABSTRACT Eclectus is one of many birds in Indonesia. The condition at captive may vary to the bird’s natural habitat. The objective of this research was to find out the comparison of daily behavior between two males Eclectus parrot at Ragunan Zoological park. Each males has different condition. The first male has a competitior in its cage, and the second male hasn’t. This research conducted January 2015 until March 2015. The behavior were ingestive, movement, motionless, and sexual. The descriptive method was used in this study. The focal animal sampling was used as a technique for recording those behavior. U Mann Whitney statistical test (p< 0,05) showed there are significant differences in the frequency of motionless and sexual behavior between male with competitor and male with no competitor. However, there is no significant diffrences in ingestive and movement behavior (p< 0,05). Keywords : Eclectus parrot, behavior, competitor, Ragunan